IL-4 and IL-13, not eosinophils, drive type 2 airway inflammation, remodeling and lung function decline. (February 2023) - Scott, George; Asrat, Seblewongel; Allinne, Jeanne; Keat Lim, Wei; Nagashima, Kirsten; Birchard, Dylan; Srivatsan, Subhashini; Ajithdoss, Dharani K.; Oyejide, Adelekan; Ben, Li-Hong; Walls, Johnathon; Le Floc'h, Audrey; et al.
Abstract: Rationale: Type 2 (T2) asthma is characterized by airflow limitations and elevated levels of blood and sputum eosinophils, fractional exhaled nitric oxide, IgE, and periostin. While eosinophils are associated with exacerbations, the contribution of eosinophils to lung inflammation, remodeling and function remains largely hypothetical. Objectives: To determine the effect of T2 cytokines IL-4, IL-13 and IL-5 on eosinophil biology and compare the impact of depleting just eosinophils versus inhibiting all aspects of T2 inflammation on airway inflammation. Methods: Human eosinophils or endothelial cells stimulated with IL-4, IL-13 or IL-5 were assessed for gene changes or chemokine release. Mice exposed to house dust mite extract received anti-IL-4Rα (dupilumab), anti-IL-5 or control antibodies and were assessed for changes in lung histological and inflammatory endpoints. Measurements and main results: IL-4 or IL-13 stimulation of human eosinophils and endothelial cells induced gene expression changes related to granulocyte migration; whereas, IL-5 induced changes reflecting granulocyte differentiation. In a mouse model, blocking IL-4Rα improved lung function by impacting multiple effectors of inflammation and remodeling, except peripheral eosinophil counts, thereby disconnecting blood eosinophils from airway inflammation, remodeling and function. Blocking IL-5 globally reduced eosinophil counts but did not impact inflammatory or functional measures of lung pathology. Whole lung transcriptome analysis revealed that IL-5 or IL-4Rα blockade impacted eosinophil associated genes, whereas IL-4Rα blockade also impacted genes associated with multiple cells, cytokines and chemokines, mucus production, cell:cell adhesion and vascular permeability. Conclusions: Eosinophils are not the sole contributor to asthma pathophysiology or lung function decline and emphasizes the need to block additional mediators to modify lung inflammation and impact lung function.